Towards Competency Based Education National Education Policy, 2020 - Sangai, Sandhya (JOURNAL OF INDIAN EDUCATION, 2021)
Competency based Education (CBE) is an outcome-based approach, which focuses on ensuring proficiency in learning in terms of skills, values, attitudes and knowledge required for real-life situations. In the context of school education, this refers to such systems of teaching-learning, assessment and academic reporting wherein students exhibit that they have learned the knowledge and skills they are expected to learn as they progress through different grades and levels of education. CBE is essentially a learner-centred approach, and teachers are the facilitators who would enable the transfer of knowledge and skills, and create a positive attitude and motivation for learning. However, in the present context, complete implementation of the principles of CBE is not possible. The system should focus on the development of appropriate ways of achieving learning outcomes for each grade and stage. The learning outcomes are expected to represent the holistic development of the learner. It is crucial to take teaching, learning and assessment together, one complementing the other and portrays a holistic picture of the child. In order to make the education system organic and responsive, the National Education Policy 2020 has suggested certain actions to be taken forward following the learning outcomes based approach.